PRA-RANCANGAN INDUSTRI EKSPOR BUAH ALPUKAT (PERSEA AMERICANA MILL.) DENGAN TEKNOLOGI ACTIVE PACKAGING: ANALISIS SIFAT FISIK ALPUKAT (PERSEA AMERICANA MILL.) PADA PROSES PENYIMPANAN METODE KEMASAN AKTIF (ACTIVE PACKAGING) MENGGUNAKAN ASAM ASKORBAT DAN KALIUM PERMANGANAT DENGAN MEDIA BATU ZEOLIT - Benita Clarissa, Abigail
This paper is an overview of research that aims to determine the best treatment variations for the concentration of L-ascorbic acid (C6H8O6), potassium permanganate (KMnO4), and the number of zeolite stones in the avocado storage process with the active packaging method based on the physical properties of the fruit in the form of percentage weight loss, level of hardness, to organoleptic texture. In general, what will be done in this research is the optimization of avocado packaging with the active packaging method which consists of 4 stages, namely 1) formulation and response design, 2) formulation, 3) response data analysis, and 4) optimization. The research design was carried out using the Minitab 19® Response Surface Methodology (RSM) Box-Behnken Design (BBD) program to determine the optimum conditions of several combinations of active packaging components on the physical properties of avocados. Based on this study, the results of the analysis of variance (ANOVA) showed that the model chosen was Full Quadratic. The results of the optimization of the best treatment variations for the concentration of L-ascorbic acid (C6H8O6), potassium permanganate (KMnO4), and the number of zeolite stones in the avocado storage process using the active packaging method based on the physical properties of the fruit in the form of percentage of weight loss, hardness level, to organoleptic texture are variations in the concentration of KMnO4 by 35%, ascorbic acid by 68.5%, and the amount of zeolite by 45 grams. Avocado fruit with this variation of treatment can maintain its quality for up to 12 days of storage at normal temperatures. Thus, it is hoped that this active packaging method can be an alternative post-harvest handling in increasing the shelf life of avocados.